I protoplasti paleocristiani dell’ordine dei monaci di san Paolo primo eremita secondo l’opera "Paulina Eremus" di Padre Bartolomeo Bolesławski - Degórski, Bazyli (Vox Patrum, 2008)
The article analyzes the manuscript work of Father Bartłomiej Bolesławski O.S.P.P.E .: "Paulina Eremus seu co [m] mentarius hystoricus in quo Ordinis Fratrum Eremitarum Sancti Pauli Primi Eremitae primordia, progressus, fundationes, privilegia, viri illustres referuntur" from year 1630. This manuscript is currently kept in the Jasna Góra Archives. Father Bolesławski’s Pauline Eremus is not only a valuable source to learn about the history of the Pauline Order, but also introduces the history of the hermitism of the first centuries of Christianity, with which Paulines have been and are closely connected to from the very beginning. Paulina Eremus provides numerous information about both the history of Old Christian hermits and the Pauline Order itself. The manuscript clearly shows that the spirituality of Pauline monks is deeply connected not only to Saint Paul of Thebes - the first Christian hermit, but also to all hermits of the first centuries - his followers.